Theoretical Dispute About the Relationship Between Interest and Growth Rates - Überblick (Wirtschaftsdienst)
Abstract Since the outbreak of the economic and financial crisis, the prolonged phase of low interest rates has been increasingly controversial. The relationship between the interest rate r and the growth rate g plays a central role in this context: some authors derive a justification for a more expansionary fiscal policy at r < g. This topic is also addressed by authors Carl Christian von Weizsäcker and Hagen Krämer in their current book, “Sparen und Investieren im 21. Jahrhundert Die große Divergenz”. They discuss the role of the determinants of interest rates in the equilibrium between savings and investments and derive policy implications. The central thesis is that the negative real interest rate is an indicator of excessive savings. This results in a call for political change, away from limiting public debt and towards a reduction of the savings surplus. Both the theory and the policy implication have elicited a great deal of attention at academic conferences. Since these debates are very instructive in the dispute between the schools of thought, this selection of essays will feature both the authors and their critics Hans-Werner Sinn, Eckhart Hein and Peter Bofinger, who will each present their views on the theory and the evidence of the topic.